How do Iranian older adults define place attachment? a qualitative study - Zahra Aliakbarzadeh Arani; Nasibeh Zanjari; Ahmad Delbari; Mahshid Foroughan; Gholamreza Ghaedamini Harouni (Tabriz University of Medical Sciences, 2021)
Background: Place attachment is the emotional bond between individuals and environment, which seems to increase wellbeing in old age. The purpose of this study was to explore the concept of place attachment from older adults' perspective. Methods: In this qualitative study, a total of 14 older adults were purposively included in Aran and Bidgool city, Isfahan, Iran. The data were collected using a semi-structured interview and analyzed applying a directed content analysis approach. Results: As participants reported, place attachment meant intensive love, pride, dependency, and familiarity with the environment. Socio-economic attachment was identified as the most prevalent dimension of place attachment, followed by affective, physical, autobiographical, and religious-cultural attachment. Conclusion: Our findings provided a new understanding of place attachment in the context of Iran. The concept of place attachment was identified with a multidimensional nature from Iranian older adults' perspective. Such a multidimensionality of place attachment should be considered while planning for age-friendly cities or the operationalization of the subject of aging in place, particularly in the developing societies, like Iran.